How the Impact of Islamic Stocks and ZIS (Zakat, Infaq & Shodaqoh) on Poverty - Abdul Holik (Owner : Riset dan Jurnal Akuntansi, 2025)
The role of Islamic stock in poverty reduction was sometimes dubious. This research empirically aims to address any questions and doubts about the impact of Islamic stocks and ZIS (zakat, infaq, & shodaqoh) in reducing poverty. The study chose the period from 2002 to 2015. It is the starting year of Islamic stocks traded in Indonesia until its peak of growth. The method used here is VAR (Vector Autoregressive), which can capture reciprocal relationships among all variables. Based on the calculation with VAR, we found that Jakarta Islamic Index (JII), as a proxy for Islamic stocks, ZIS and poverty have a negative impact reciprocally. The Granger-Causality test shows that all variables have a significant impact on influencing each other. In this research, we propose that stock markets do not directly eradicate poverty, but through the mechanism of capitalisation in real sectors. Meanwhile, ZIS, as an Islamic philanthropy, can provide a direct impact on the poor to improve their welfare.